The impact of altitude on screening for critical congenital heart disease. (May 2018) - Paranka, Michael; Brown, Jeffrey; White, Robert; Park, Matthew; Kelleher, Amy; Clark, Reese
Abstract Objectives The objectives were to determine the frequency with which pulse oximetry identifies critical congenital heart defects in asymptomatic full-term and late preterm newborns using the AAP expert panel algorithm in a variety of different hospital settings and to evaluate the impact of altitude on the rate of positive screens. Methods We conducted a prospective clinical study of implementation of a newborn pulse oximetry screening for congenital heart disease in 34 independent hospitals. Infants were eligible for enrollment if their gestational age was 35–44 weeks. Results Of the 34 sites which enrolled infants into our study, 24 were located at or below 2000 feet; 5 were located between 4700 and 6000 feet and 5 were located above 6000 feet in altitude. We screened 6109 infants; 65 (1.1%) had a positive screen. There were no differences in median gestational age, birth weight, mode of delivery or race/ethnicity for infants with a positive screen compared to infants with a negative screen. Infants with positive screens were more often male and more often born at sites located at high altitudes. The frequency of a positive screen increased from 0.2% for infants born at sites at or less than 2000 feet to 6% for sites located above 6000 feet. We stopped enrollment at the site located at 8163 feet after enrolling 65 infants because 23 (35%) were positive. Conclusions Screening infants for critical cardiac defects at altitude is complicated by the increased false positive screens.